Harnessing Soybean Diversity: Evaluating Introduced Genotypes for Sustainable Yield in Pakistan - Nain, Zulqar; Ahmed, Zaheer; Raza, Ahmed; Ali, Maqsood; Ahmad, Uzair; Arif, Faiz Ullah; Nasir, Muhammad; Qasim, Muhammad; Muhammad Rizwan Shafiq; Iqbal, Sidra (Journal of Agriculture and Veterinary Science, 2026)
Food security has become a challenging issue in the altered climate pattern, especially for developing countries. Soybean (Glycine max L.), a crop having high protein and edible oil content, has great potential but remains underutilized in Pakistan due to the lack of diverse, locally adapted genotypes. This study aimed to assess the genetic potential of fifteen exotic soybean genotypes, including one check cultivar, Faisal Soybean, by investigating various yield-related traits under the agroclimatic conditions of Okara, Pakistan. This experiment was conducted under a Randomized Complete Block Design (RCBD) with three replications. Analysis of variance revealed highly significant (p < 0.01) genetic variation for plant height (MS = 93.58), number of pods per plant (MS = 152.46), and number of seeds per pod (MS = 1.407). Principal component analysis (PCA) showed that the first two components accounted for 73.02% of the cumulative variability in quantitative traits and 86.12% in qualitative traits, with plant height and pods per plant identified as key yield-related contributing traits. Positive correlations were observed among several traits, such as plant height, primary branches (r = 0.64), pods per plant (r = 0.41), and seeds per pod (r = 0.62). Cluster analysis grouped the genotypes into distinct clusters, with genotypes G1, G10, and G11 showing unique characteristic profiles, while G4, G5, G13, and G15 formed a closely related group. These findings highlight considerable genotypic variation in major traits, contributing to the development of high-yielding, climate-resilient varieties adapted to local conditions.
Keywords: Soybean; Genotypic Variation; Yield Traits; Principal Component Analysis; Cluster Analysis